Chronic myelogenous leukemia coexpressing V-e16a2, V-e13a2, e13a2, and e14a2 BCR::ABL1 fusion transcripts: a case report and review of the literature - Xu, Yang; Fan, Yuying; Liu, Sijin; Chang, Jianmei; Guo, Caifeng; Chen, Lanhui; Guo, Wenzheng; Dang, Jinwen; Wang, Hongwei; Tan, Yanhong (Frontiers in Oncology, 2024)
The coexistence of three or more transcripts in one patient with chronic myeloid leukemia (CML) is rarely reported. Thus, the disease progression and drug response are still unknown. This case report aimed to explore the drug response of CML with variant transcripts and to enrich the clinical treatment of rare types of CML. A 66-year-old Chinese female patient was diagnosed with chronic myeloid leukemia-chronic phase (CML-CP) expressing four BCR::ABL1 transcripts, including variant e16a2(V-e16a2), variant e13a2(V-e13a2), classical e13a2, and e14a2 transcripts. The patient was treated with flumatinib, a tyrosine kinase inhibitor (TKI).The variant transcripts reported exhibited a favorable response to TKI, and attention should be directed toward monitoring variant transcripts.